The BPS-UP General High School Administrative and Supervisory Personnel Development Program an evaluation - Guardian, Anita Angeles 1928- (1976)
Evaluation data from 92 program grantees from 11 regions showed that the objectives of the program were attained satisfactorily, upgrading administrators and supervisors who gained knowledge on the latest trends in the teaching of such subject areas as reading, social studies, science, and mathematics. The respondents reported changes in their values, attitudes and perspectives which affected their administrative functions and brought about a better understanding of the principles of administration, fostered closer relationships between teachers and engendered more tact in dealing with subordinates and greater understanding of the faults of others.
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: School superintendents and principals, Training of -- Philippines